Clinicopathological and prognostic impact of imaging of breast cancer angiogenesis and hypoxia using diffuse optical spectroscopy. Issue 7 (27th June 2014) - Nakamiya, Noriko; Ueda, Shigeto; Shigekawa, Takashi; Takeuchi, Hideki; Sano, Hiroshi; Hirokawa, Eiko; Shimada, Hiroko; Suzuki, Hiroaki; Oda, Motoki; Osaki, Akihiko; Saeki, Toshiaki
<x xml:space="preserve">Abstract</x> Near‐infrared diffuse optical spectroscopy (DOS) imaging can non‐invasively measure tumor hemoglobin concentration using high contrast to normal tissue, thus providing vascularity and oxygenation status. We assessed the clinical usefulness of DOS imaging in primary breast cancer. In all, 118 women with a histologically confirmed diagnosis of primary malignant tumor were enrolled. All participants underwent testing using time‐resolved DOS before treatment initiation. Visual assessment of DOS imaging for detecting tumors was carried out by two readers blinded to the clinical data. Relative total hemoglobin (rtHb) and oxygen saturation (stO2) of the tumors was compared with clinicopathological variables and 10‐year prognosis was calculated. Sensitivity for detecting a tumor based on the rtHb breast map was 62.7% (74/118). The sensitivity depended on T stage: 100% (7/7) for T3, 78.9% (45/57) for T2, 44.7% (17/38) for T1, and 31.3% (5/16) for Tis. Tumors showed unique features of higher rtHb with a wider range of stO2 than normal breast tissue, depending on histological type. There was a significant correlation of rtHb with tumor size, lymphatic vascular invasion, and histological grade, and of stO2 with age and tumor size. Neither rtHb nor stO2 correlated with intrinsic biomarkers such as estrogen receptor, progesterone receptor, or human epidermal growth factor receptor 2; rtHb inversely correlated with 10‐year relapse‐free survival and overall survival, with statistical significance. Diffuse optical spectroscopy imaging has limited utility for the early detection of breast cancer; nonetheless, the findings suggest that the degree of tumor angiogenesis and hypoxia may be associated with tumor aggressiveness and poor prognosis.